Pig production costs halved - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The use of locally-available raw materials has halved the cost of pig production in the Solomon Islands. In trials funded by the Overseas Development Administration's Geographical Divlsion, local copra meal, cassava and fishmeal were fed to pigs...